Augmented reality hologram - Shiro Takeguchi (Nanyang Technological University, 2020)
A mobile application designed with the idea of using existing Augmented Reality tools. The application is based on an existing application known as ARHolo. The project prior was focused in developing the application suitable for Android OS users. However, the project is now made to accommodate the other side of the user base, Apple iOS. The project fills in the gaps of current Augmented Reality applications in its ability to render multiple holographic objects on a single augmented plane, gaining access to more AR objects through online resources and even creating their own AR object. As such, we will be working to create ARHolo on iOS and have similar functionalities as those on its Android equivalent.